Discriminação e decoerência: um modelo em caviades de microondas - Roque Teles Frade Paulinelli (2012)
We have studied the evolution of a q-bit monitored by a dispersive probe submitted to dissipation. Both are mapped on a two-level atom "dressed" by a coherent eld in the high detuning regime of the Jaynes-Cummings model. A monomodal eld, created inside of a superconducting cavity, is constantly fed by a classical microwave source. The dynamics is governed by a markovian master equation in the weak-coupling limit, where the environment is modeled by innity harmonic oscillators non-interacting with each other. The atom, prepared in a superposition, has its path marked by a eld through nonorthogonal states and, therefore, only partially distinguishable. The dissipative dynamics has three distinct regimes in respect of loss of coherence in which the atom-eld interactionis xed and the dissipation constant is varied. Despite these regimes have a direct classical analogue, essentially quantum eects such as "freezing" of the atom-eld interaction occur due to increased dissipation. An experimental implementation to quantify the which-way discrimination through atomic visibility measures is suggested